Template for article construction: Article template - BJPE, Revista (Brazilian Journal of Production Engineering, 2020)
The current system, used by the journal, requires the author(s) to indicate (in) 3 potential reviewers for their manuscript, and they must not belong to their institution. The indication must occur in the "Author’s Comments" field or as "Docs. sup.", containing: FULL NAME, ORCID, Practice Area, TITLE, E-MAIL and Institution/Affiliation. The author(s) may also indicate non-preferred reviewers. It is up to the Associate Editor to accept or reject this indication. 🇧🇷 THE TEXT FOLLOWS THE STANDARDS OF STYLE AND BIBLIOGRAPHICAL REQUIREMENTS DESCRIBED IN "GUIDELINES FOR AUTHORS" (TEMPLATE) ABOVE AND REGARDING THE APA: GENERAL RULES OF STYLE AND FORMATTING. (Area of Electronic Resources and User Support Library of the University of Aveiro, 2010). Text alignment must have justified formatting, without header, footer, footnotes, or page number. The paper format must be A4, with top and bottom, right and left margins of 2.5 cm. The document font is Time News Roman, size 12. Paragraphs are not indented, with 0 pt spacing. and, later, of 6 pt. Line spacing is 1.15, except in special cases. Sections can have subsections and these still have three more levels of subdivisions. As an example: 4.2.3 METHODOLOGY designates the third subdivision of the second subsection of section 4. The use of images, equations, tables and illustrations must follow common sense and, preferably, the ethics and axiology of the scientific community that discusses the themes of the manuscript. Tables, Charts & Graphs: same font as the body of the text, size 10, line spacing 1.0, spacing before and after 0 pt. Captions positioned at the top, size 12, line spacing 1.0, front and back spacing 0 pt. QUOTES The method employed by the APA Standards is author-date, that is, the author’s surname and year of publication. The text must be documented citing the author and publication date of the researched and consulted works. All authors cited in the text, and only them, must be present in the references with complete information. This procedure is mandatory. The complete list of references must be presented at the end of the text and in alphabetical order by the last name of the first author. They must be justified, edited with 1.00 spacing between lines, without spacing before and 6pt after between paragraphs. Follow guidelines: http://www.anpad.org.br/rac/rac_guia_apa.pdf After proper evaluation of the manuscript by the reviewers, in addition to following the suggestions of the reviewers, it is necessary to check for signs of plagiarism through the CopySpider Software, available at http://www.copyspider.com.br/main/ , and send us the report showing that the article has a maximum of 3% similarity with other files (and justification if greater than 3%). The current system, used by the journal, requires the author(s) to indicate (in) 3 potential reviewers for their manuscript, and they must not belong to their institution. The indication must occur in the "Author’s Comments" field or as "Docs. sup.", containing: Full Name, Title, Orcid, E-Mail and Institution/Affiliation. The author(s) may also indicate non-preferred reviewers. It is up to the Managing Editor to accept or reject this indication.